The influence of osmotic pretreatments on melon (cucumi smelo l.) quality during frozen storage (2014)
ABSTRACT The aim of work was to evaluate the influence of using OD on drip loss (DL), volume (V), total color change (ΔE), and firmness of Cucumis melo L. samples (Cantaloupe variety), stored under freezing conditions. The samples were frozen up to two humidity levels (75% and 85%, b.h.), using an osmotic sucrose solution with 55ºBrix, at 27± 0.2ºC. The dehydrated samples were frozen at -40ºC and then stored at -18ºC for 1, 15 and 30 days. Fresh fruit samples (non-osmotic treatment) were used as control along the freezing storage time period. The results showed that the treated samples had significantly (p